Impact of structured physical activity program on the level of functional ability of Persons with Mental Illness - Rinku Kumari Gorain; Rajalakshmi Ramu; Preeti Sinha; Radhakrishnan Govindan (Wolters Kluwer Medknow Publications, 2022)
BACKGROUND: A structured physical activity program has many health benefits. Physical activity improves the functional ability of a patient with mental illness as an adjunctive treatment. This study aimed to evaluate the efficacy of a physical activity program on the level of functional ability of patients with mental illness. MATERIALS AND METHODS: A pre-experimental research design and one group pre-post design were adopted. Thirty-one in-patients with mental illness who met the inclusion criteria were recruited for the study using convenient sampling. Baseline data were collected using sociodemographic and illness profiles developed by the researcher and validated by the experts. Functional ability and illness severity were assessed using the standardized World Health Organization Disability Assessment Schedule (WHODAS) (36-item version) and the Clinical Global Improvement Scale. Pretest, i.e., intervention with structured physical activity, was administered for 40 consecutive days. A posttest was given 30 days after the intervention ended to assess the impact of the structured physical activity program on the level of functional ability among the study participants. RESULTS: The impact of structured physical activity on functional ability was measured using the WHODAS 2.0, a 36-item version. The paired Sample t-test and the Wilcoxon Rank test analyzed the data. There was a significant improvement in the overall functional ability of study participants at P = 0. 001. CONCLUSION: The study findings support that structured physical activity substantially impacts functional ability among patients with mental illnesses.